Object Detection and Filtering Techniques of Underwater Images : A Review - Martin, Martina; Mishra, Nischol (International Journal of Computer Sciences and Engineering, 2019)
As going deep under the water nothing can be seen properly as well as it is difficult to identify any substance residing or present under water. This survey basically focuses on the detection of the underwater image which are taken through various self-ruling submerged vehicles and remotely controlled vehicles, in order to improve the quality of the pictures. The factors include the low contrast, blur, non-uniform lighting and faded colors. This paper analyzed an image enhancement technique along with the image restoration technique that will help to acquire images that are of better quality. The algorithms applied on the degraded images comprises of two domains- Spatial Domain Methods, Frequency Domain Methods. The literature reviews used in this paper explained that the preprocessing algorithms used by various authors uses a standard filter techniques contain different combinations. The survey includes analysis in terms of qualitative and quantitative factors on hundreds of underwater images. The images taken in offshore water characterized by a heavy concentration of colored dissolved organic matter and total suspended matter, thus various methods have been applied on the images in a proper way so as to obtain a fresh image.